IMF Staff Papers, Volume 50, No. 3 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2003)
This paper analyzes the issue of purchasing power parity using real effective exchange rate (REER) data for 20 industrial countries in the post-Bretton Woods period. The serial correlation-robust median-unbiased estimator yields a cross-country average of half-lives of deviations from parity of about eight years, with the REER of several countries displaying permanent deviations from parity. The paper analyzes integration of Africa into world trade. The high-yield spread as a predictor of real economic activity is also examined.